Evaluation of Anemia as a Risk Factor for Lower Respiratory Tract Infection in Children - Toqeer Ahmad, Allah Nawaz Sultan, Shabir Ahmed, Nosheen Iftikhar, Waheed Ahmad, Atif Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute lower respiratory tract infection being a leading cause of death n children less than five years of age and anemia is the commonest cofactor in these patients seeking medical advice, particularly in developing countries. Aim: To determine the association of anemia with lower respiratory tract infection in children by evaluating the frequency of anemia in children with and without LRTI. Methods: A Case Control Study was carried out at department of Pediatrics, Children hospital Lahore, Institute of child health from 20-1-18 to 20-7-19. Blood was drawn by phlebotomist from each patient included in this study by using disposable and sterile syringes and accurate tubes. Blood samples were used to estimate hemoglobin level by using automatic blood cell counter. Anemia was defined as per operational definition. Children were managed as per standard protocol. Results: In this study risk of anemia was significantly higher among cases i.e. Cases: 54% & Controls: 22%, OR= 4.162, p-value=0.001. Although in all age groups frequency as well as risk of anemia was higher in cases. But children among cases in the elder age group showed statistically significant risk for anemia as compared to children in control group i.e. 31-45 Months. OR= 14.00, p-value=0.013 & 46-60 months: 5.60, p-value=0.027. Conclusion: Children presenting with LRTI possesses significant risk for anemia. Thus, early and accurate diagnosis of anemia in children and treatment of anemia will have a positive effect decreasing pneumonia in children.